Development Program on Digital Marketing and Brand Strengthening for Cellular Businesses in Gunungkidul Regency - Candra Eka Prasetiya; Audita Nuvriasari; Azwar; Nurul Putri Ardiani; Mifta Ul’Ulum (Faculty of Economics Universitas Sarjanawiyata Tamansiswa, 2022)
The development of communication technology has boosted the level of business competition, one of which is SMEs selling mobile phones. Msellular & Apple Store is one of the SMEs engaged in mobile phone trading and is located in Wonosari, Gunungkidul, DIY. The business problems faced by Msellular & Apple Store are (1) Social media as an online marketing tool has not been used optimally (2) The identity or brand of the store is not well known by the local community (3) There is no customer database that can be used as a source of marketing programs. The solution to solve that problem are: (1) Optimizing the use of social media through improving design and content, (2) Strengthening store branding through collaboration with other parties and (3) Develop a customer database based on information technology. The methods used in this program are: (1) counseling, (2) training and (3). Mentoring. The counseling carried out is educating partners about strategies for strengthening brands and expanding cooperation networks. Training activities include: (1). content creation for marketing through social media and (2). create a customer database based on IT. Mentoring is intended to monitor program implementation. The results of this activity are: (1). content on social media is increasingly attractive and used as a marketing tool, (2). the establishment of cooperation with other parties to strengthen the store brand and (3). availability of customer database to support marketing activities.